The EU Water Framework Directive: Challenges and Prospects for Implementation in Ukraine - Yara, Olena; Uliutina, Olena; Golovko, Liudmyla; Andrushchenko, Liliiy (European Journal of Sustainable Development, 2018)
The purpose of our scholarly work is to carry out the analysis of main trends of development and features of harmonization of Ukrainian water legislation with the EU Water Framework Directive (WFD). Limited analysis of the WFD was made and challenges for its implementation in Ukraine were explored. Our study is organized around three major themes: river basin management, water resource protection and water monitoring. As a result of the study proposals for the improvement of Ukrainian environmental legislation were made. Based on comparison analysis differences and common problems of implementation of the WFD in Ukraine and EU member states were determined and recommendations for implementation of successful experience of EU countries in Ukraine were made. Keywords: EU water policy, water legislation, water management, water quality, water resources